2020
DOI: 10.1080/08927014.2020.1739271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a sub-minimum inhibitory concentration of chlorhexidine gluconate on the development of in vitro multi-species biofilms

Abstract: Quantification of single-species biofilms using crystal violet assayThe quantification of single-species biofilms of Streptococcus mutans (S. mutans) UA159, Actinomyces naeslundii (A. naeslundii) ATCC12104, and Streptococcus oralis (S. oralis) ATCC35037 against chlorhexidine gluconate (CHG) at sub-minimum inhibitory concentration (sub-MIC) was performed using the crystal violet (CV) assay (Figure S1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The antiseptics used included ve different CHX salts (digluconate 33,35,37,40,47,50,[55][56][57][58]61,63,67,69,74,75,81,83,88,90,94,97,99,101,106,107,111,113 , gluconate 34,36,42,42,53,91,102,103,108,108,109,112 , dichlorohydrate 85-87 , diacetate 71,99 and dihydrochloride 96 ) and povidone-iodine 37,46,49,70,76,91 . In total, MBC data from 6218 microbes were extracted.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiseptics used included ve different CHX salts (digluconate 33,35,37,40,47,50,[55][56][57][58]61,63,67,69,74,75,81,83,88,90,94,97,99,101,106,107,111,113 , gluconate 34,36,42,42,53,91,102,103,108,108,109,112 , dichlorohydrate 85-87 , diacetate 71,99 and dihydrochloride 96 ) and povidone-iodine 37,46,49,70,76,91 . In total, MBC data from 6218 microbes were extracted.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…When controlling for resistance to methicillin (MRSA vs MSSA), there was still no evidence of a change in the MBC over time (β 0.26 [-0.87, 1.34]; I 2 99%). Study level estimates for MSSA, MRSA and coagulasenegative Staphylococci are shown in S1 Fig.Overall, 25 studies reported the MBC of CHX for Streptococci species; observations of viridans Streptococci were most common44,45,47,48,[52][53][54]58,66,69,75,[77][78][79]81,82,[84][85][86]89,99,100,103,105,106 and 1 study 106 provided an estimate for Streptococcus pyogenes (Lance eld group A). The pooled mean MBC of CHX for Streptococci was 8.54 mg/L (95% CI 4.75, 12.3; I 2 99%).…”
mentioning
confidence: 99%
“…Articles were published between 1976 and 2021, although the majority (95%) were published this century. The antiseptics used included five different CHX salts (digluconate (33,35,37,40,47,50,(55)(56)(57)(58)61,63,67,69,74,75,81,83,88,90,94,97,99,101,106,107,111,113), gluconate (34,36,42,42,53,91,102,103,108,108,109,112), dichlorohydrate (85)(86)(87), diacetate (71,99) and dihydrochloride( 96)) and povidone-iodine (37,46,49,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In other words, the biofilm cannot be removed only by immersion in the mouthwash. In one study, there was a report that the effect of chlorhexidine digluconate on biofilms caused a concentration gradient in the antimicrobial component, which was below the minimum inhibitory concentration and enhanced biofilm formation [20].…”
Section: Introductionmentioning
confidence: 99%